THE SIGNIFICANCE OF POLITICAL STABILITY IN RURAL DEVELOPMENT AGENDA IN MATUNGGONG, SABAH - Romzi Ationg; Mohd. Sohaimi Esa; Irma Wani Othman; Saifulazry Mokhtar (Journal of Islamic, Social, Economics and Development, 2021)
Many suggests that the sub-district of Kudat which is also part of the Kota Marudu parliamentary constituency namely Matunggong in Sabah have been the area generally affected by poverty. Some even portrays Matunggong as an area in which the agenda of rural development have been slow paced due to numbers of factors. It includes political development there which characterises by the propensity of political leadership changes during elections because of conflicts or rampant competition between various political parties as well as rivalry within the party. Having said that, however, the linkage between political development and specifically political stability, and the slow paced of rural development in Matunggong, Sabah, Malaysia has never been discussed systematically through the lens of academic. By applying a qualitative approach through the examination of information gathered from various sources such as books, journals and media reports as well as interview with selected respondents, the paper presents a discussion on the the significance of political stability in rural development agenda in Matunggong of Sabah, Malaysia. The findings are expected to contribute in the systematic understanding of linkages between political stability and rural development agenda, thus provides fundamental information on the way the rural area should be developed by the development agencies and specifically the political leaders.